IMPROVEMENT OF PBSI SEMESTER STUDENTS CAPABILITY VI IN WRITING SCIENTIFIC ARTICLES THROUGH THE PROCESS APPROACH ON WRITING SKILLS - Yulianah Prihatin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The research is aimed to know the process of learning the skills to write articles by students PBSI VI semester University Hasyim Ashari thorough approach to the process, barriers s ver the process of learning as well as the effectiveness of the approach to the process in the process of learning to write. Research is shortly g using design PTK with 2 cycles. The results of the research are, first, the learning process runs according to the plans that have been prepared. In cycle 1 consists of planning, implementation ( introduction, core, and closing ), while in cycle II, it consists of re-planning and implementation ( introduction, core, and closing ). The results of the second, namely, the barriers were experienced among which several references have not been prepared by lecturers, students who arrive late, students who are not active in disguise group, indoor heat, sound noisy at the outside of class. These obstacles are not the same every cycle. Third, the process approach is proven to be able to improve students' abilities in making scientific articles. Through the approach of the process, how to write the students more focused and gradual. This increase can be proven from the average value of the class which was originally 55 in the initial condition to 75 in the first cycle and 80 in the second cycle.